Dietary index for gut microbiota and hypertension risk: a cross-sectional NHANES study - Che, Xiaona; Li, Xinqi; Na, Lin; Sun, Yunfei; Kong, Ziang; Cui, Wenjing; Chang, Jing; Xue, Xin (Frontiers in Nutrition, 2025)
BackgroundGut microbiota’s role in hypertension is emerging, but systematic studies on microbiota-linked dietary indices (DI-GM, BGMS, UGMS) remain limited.MethodsThis study leveraged data from the National Health and Nutrition Examination Survey (NHANES) database spanning 1999–2020. A cross-sectional study design was employed to gather baseline information from 41,193 adult participants aged 20 years and older, encompassing sociodemographic characteristics and health-related factors. To investigate the associations between DI-GM, BGMS, UGMS, and the prevalence of hypertension, weighted logistic regression models, restricted cubic spline (RCS) analysis with three knots (positioned at the 10, 50, and 90th percentiles of the independent variables), and subgroup analyses were performed.ResultsThe study findings demonstrate that both DI-GM and BGMS are significantly and inversely associated with the prevalence of hypertension. Specifically, each one-unit increase in DI-GM was linked to a 4% reduction in hypertension risk (OR = 0.96, 95% CI: 0.94–0.98, p < 0.001), and each one-unit increase in BGMS was associated with a 5% decrease in hypertension risk (OR = 0.95, 95% CI: 0.92–0.97, p < 0.001). Further RCS analysis demonstrated a linear relationship between DI-GM and BGMS with hypertension risk. Additionally, subgroup analyses stratified by age, gender, BMI, and diabetes status exhibited robust results (P for interaction >0.05).ConclusionDI-GM and BGMS exhibit significant inverse associations with hypertension prevalence, with BGMS displaying a stronger protective effect. No significant relationship was identified between UGMS and hypertension.